(untitled) (Research, Society and Development, 2020)
Objective: to analyze the microbiological characteristics of the water consumed by the population of Piripiri, checking the presence of E. coli and total coliforms in the water ingested by the inhabitants of the city of Piripiri and defining means of prevention for possible pathologies due to the ingestion of contaminated water. Methodology: This is a qualitative and quantitative study, in which water was collected in the cauldron reservoir, in the artesian well of the Luiz Meneses municipal road located in the Garibaldi neighborhood and in four residences in the neighborhoods: Floresta, Prado, Petecas and Centro located in the municipality of Piripiri. Right after the collections, the samples were sent for microbiological analysis at the 3rd Piripiri Health Regional. Results: the presence of total coliforms and E. Coli in samples from Açude Caldeirão and Petecas is noted. In the Prado and Floresta neighborhoods, they presented only total coliforms. In the quantitative analysis according to the most likely number technique per deciliter, the Açude Caldeirão presented> 8.0 and total coliforms and E. Coli; Floresta e Petecas 8.0 and Prado 1.1 both only the presence of total coliforms. Conclusion: it was possible to observe that in 80% of the water samples from the municipality of Piripiri it is contaminated and consequently this improper for human consumption caused by a possible failure in the treatment of that water, being necessary the use of different means for the decontamination of this water.